Let us define a function $f(k,n)$ by

\begin{equation} f(k,n)=n \left (\cos\frac{k\pi}{n}\right) \left(1-\cos\frac{k\pi}{n}\right) - \sin \frac{k\pi}{n} \end{equation}

where $\frac{k}{n}$ is irreducible with $k,n \in \mathbb{N}$, with $k \leq \left \lfloor{n/2}\right \rfloor$, and $k \geq 2,$ $n \geq 5$.

I suspect that $f(k,n) >0$.

Plugging in a few values of $k$ and $n$ and computing $f(k,n)$ numerically indeed shows that, but how do I prove / disprove this?

  • $\begingroup$ This is connected to the concept of irrationality measure. $\endgroup$ – Lucian Feb 26 '16 at 7:00
  • $\begingroup$ Have you tried showing that $n\cos\theta (1-\cos\theta)-\sin\theta>0$ for $\frac{\pi}{n}\leq \theta <\frac{\pi}{2}$? $\endgroup$ – Bobby Grizzard Feb 26 '16 at 20:50
  • $\begingroup$ I mean for $\frac{\pi}{n}\leq \theta \leq \frac{\pi}{2}-\frac{\pi}{n}$ $\endgroup$ – Bobby Grizzard Feb 26 '16 at 21:07

Proof: Since $\frac{k}{n}$ is irreducible and $k\le \lfloor \frac{n}{2}\rfloor$, we have $k \le \frac{n-1}{2}$.

Let $u = \tan \frac{k\pi}{2n}$. Since $2\le k \le \frac{n-1}{2}$ and $n\ge 5$, we have $$0 < \frac{\pi}{n} \le \tan \frac{\pi}{n} \le u \le \tan \Big(\frac{\pi}{4} - \frac{\pi}{4n}\Big) = \frac{1 - \tan \frac{\pi}{4n}}{1 + \tan \frac{\pi}{4n}} \le \frac{1-\frac{\pi}{4n}}{1+\frac{\pi}{4n}} < 1.$$ Using $\cos \frac{k\pi}{n} = \frac{1-u^2}{1+u^2}$ and $\sin \frac{k\pi}{n} = \frac{2u}{1+u^2}$, we have $$n \Big(\cos \frac{k\pi}{n}\Big) \Big(1 - \cos \frac{k\pi}{n}\Big) - \sin \frac{k\pi}{n} = \frac{2u(-nu^3-u^2+nu-1)}{(u^2+1)^2}.$$ It suffices to prove that $-nu^3-u^2+nu-1 > 0$. To proceed, we need the following fact.

Fact 1: For each positive integer $n$, $f_n(x) = -nx^3 - x^2 + nx - 1$ is concave on $[0, 1]$ since $f_n''(x) = -6nx - 2 < 0$ for $x > -\frac{1}{3n}$. As a result, for $0\le a \le x \le b \le 1$, we have $f_n(x) \ge \min(f_n(a), f_n(b))$.

Now, according to Fact 1, letting $a = \frac{\pi}{n}$ and $b = \frac{1-\frac{\pi}{4n}}{1+\frac{\pi}{4n}}$, since $0 < a \le u \le b < 1$, it suffices to prove that $f_n(\frac{\pi}{n}) > 0$ and $f_n(\frac{1-\frac{\pi}{4n}}{1+\frac{\pi}{4n}}) > 0$. We have $f_n(\frac{\pi}{n}) = -\frac{\pi^3}{n^2}+\pi-\frac{\pi^2}{n^2}-1 \ge -\frac{\pi^3}{5^2}+\pi-\frac{\pi^2}{5^2}-1 > 0$ and \begin{align} f_n(\frac{1-\frac{\pi}{4n}}{1+\frac{\pi}{4n}}) &= \frac{2n^3}{(4n+\pi)^3}\Big(-\frac{8\pi^2}{n}+32\pi - \frac{\pi^3}{n^3}-\frac{4\pi^2}{n^2}-\frac{16\pi}{n}-64\Big)\\ &\ge \frac{2n^3}{(4n+\pi)^3}\Big(-\frac{8\pi^2}{5}+32\pi - \frac{\pi^3}{5^3}-\frac{4\pi^2}{5^2}-\frac{16\pi}{5}-64\Big)\\ &> 0. \end{align} This completes the proof.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.